1997
DOI: 10.1038/sj.bjp.0701544
|View full text |Cite
|
Sign up to set email alerts
|

Neuropeptide Y (NPY) and peptide YY (PYY) effects in the epididymis of the guinea‐pig: evidence of a pre‐junctional PYY‐selective receptor

Abstract: 1 The e ects of peptide YY (PYY), neuropeptide Y (NPY) and structurally related peptides upon ®eld stimulation-induced and phenylephrine-mediated contractile responses in the cauda epididymis of the guinea-pig were investigated. 2 Preparations of cauda epididymis responded to ®eld stimulation with contractions which were completely attenuated by both the neurotoxin, tetrodotoxin (500 nM), and also by the a-adrenoceptor antagonist, phentolamine (3 mM). PYY (n=7) and the truncated peptide analogue PYY(3 ± 36) (n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

1998
1998
2002
2002

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 34 publications
2
12
0
Order By: Relevance
“…At the pre-junctional level these agonists inhibit neurotransmitter release (and electricallyevoked contractions), and at a post-junctional level they potentiate response to exogenously applied phenylephrine (Haynes & Hill, 1996;Haynes et al, 1997;1998a,b). That the post-junctional potentiation of contractile responses by G i/ocoupled receptor agonists is a receptor-selective event rather than a non-selective increase in tissue contractility is evident from the ®nding that A 1 adenosine receptor agonists do not potentiate responses to ATP (Haynes et al, 1998a).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…At the pre-junctional level these agonists inhibit neurotransmitter release (and electricallyevoked contractions), and at a post-junctional level they potentiate response to exogenously applied phenylephrine (Haynes & Hill, 1996;Haynes et al, 1997;1998a,b). That the post-junctional potentiation of contractile responses by G i/ocoupled receptor agonists is a receptor-selective event rather than a non-selective increase in tissue contractility is evident from the ®nding that A 1 adenosine receptor agonists do not potentiate responses to ATP (Haynes et al, 1998a).…”
Section: Discussionmentioning
confidence: 99%
“…We have used a methodology similar to that used in earlier studies (Haynes & Hill, 1996;Haynes et al, 1997;1998a,b) such that the a 2 -adrenoceptor agonist, xylazine, the neurotransmitter, neuropeptide Y, and the A 1 adenosine receptor agonist, CPA were all used to potentiate responses to low concentrations of the a 1 -adrenoceptor agonist, phenylephrine. Brie¯y, preparations of epididymis were set up for contractility studies, as described above.…”
Section: E Ect Of Agonist Upon Threshold Responses To Phenylephrinementioning
confidence: 99%
See 1 more Smart Citation
“…It seems clear that the postjunctional synergetic effects of NPY are more likely caused by activation of NPY Y 1 receptors (Westfall, Yang & Curfman‐Falveg, 1995; Donoso et al ., 1997b; Han et al ., 1998). Leu 31 Pro 34 neuropeptide Y (LP‐NPY), a selective NPY Y 1 receptor agonist (Fuhlendorff et al ., 1990) appears to produce similar postjunctional effects to NPY at the vascular sympathetic neuroeffector junction (Westfall et al ., 1995; Westfall, Yang, Rotto‐Perceley & Macarthur, 1996; Haynes, Hill & Selbie, 1997; Han et al ., 1998). In contrast to NPY, LP‐NPY causes no physiological inhibition of transmitter releases in the sympathetically innervated epididymis of the guinea‐pig (Haynes et al ., 1997).…”
Section: The Effects Of Npy On Postjunctional Receptorsmentioning
confidence: 99%
“…Our observation that both a LyNPY-positive neuron and a CDCH-positive neuron in the visceral ganglion project their axon into the nervus intestinalis, which also innervates the reproductive tract (including the accessory sex glands), provides additional evidence that LyNPY plays a role in regulating activity of the accessory sex glands. In vertebrates it has also been found that NPY plays a role as a modulator of neuroendocrine functions not only at the central, but also at the peripheral level, as demonstrated by its role in the innervation of the epididymis in the male (39). Recently, published data have shown that the reproductive status of female rats also influences the level and number of neurons expressing galanin (GAL)m-RNA in the nucleus paraventricularis of the brain, whereas it does not affect the hypothalamic NPY neurons (40).…”
Section: Discussionmentioning
confidence: 99%